ISLAM SEBAGAI PANDUAN FILSAFAT KONTEMPORER - Majid, Mohamad Arif (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2020)
slam and philosophy are two different terms in which the first refers to a religion, which absolute truth overcomes all space and time, brought by Allah’s most beloved Prophet, Muhammad SAW. The latter represents human activity in utilizing their intellect, optimizing their consciousness to reach understanding on any existence. Thus, this paper attempts to explore the belief that Islam must have established a set of implementation and technical guidance for philosophy. This paper aims to avoid ambiguity and confusion to determine the truth as seen in the history of philosophy. This paper argues that Islamic philoshopy provides an alternative to tackle with crisis as a result of ambiguity that rooted in the contemporary philosophy.Keywords: Islam, Contemporary Philosophy, Humanity